2009
DOI: 10.1016/j.jada.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Limited English Proficiency Is a Barrier to Receipt of Advice about Physical Activity and Diet among Hispanics with Chronic Diseases in the United States

Abstract: The prevalence of obesity, diabetes, and cardiovascular disease is reaching epidemic proportions among Hispanics in the United States. Health care providers play an important role in motivating patients to make healthful lifestyle changes to reduce the burden of such conditions. Data from the US 2000 National Health Interview Survey was analyzed to determine differences in report of physician-provided physical activity and/or dietary advice by level of English proficiency among obese Hispanics or those who rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…3 Many obstacles contribute to this disparity, including socioeconomic status, access to care, and language barriers. [4][5][6][7][8][9] To reach Latinos and other underserved groups, innovative interventions must be designed; mobile health may be just that solution.…”
Section: Introductionmentioning
confidence: 99%
“…3 Many obstacles contribute to this disparity, including socioeconomic status, access to care, and language barriers. [4][5][6][7][8][9] To reach Latinos and other underserved groups, innovative interventions must be designed; mobile health may be just that solution.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic diseases in the USA occur at disproportionately higher rates in the Hispanic population (Lopez-Quintero, Berry, & Neumark, 2009). There are numerous Hispanic immigrants who come to the USA with healthy diets and levels of high physical activity, but there is evidence that through acculturation there is a negative impact on their nutrition and exercise (Ayala, Baquero, & Klinger, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous Hispanic immigrants who come to the USA with healthy diets and levels of high physical activity, but there is evidence that through acculturation there is a negative impact on their nutrition and exercise (Ayala, Baquero, & Klinger, 2008). Health care providers have had difficulty conveying the importance of nutrition and physical activity to the Hispanic population (Lopez-Quintero et al, 2009). Researchers have found that if the health information is presented to Hispanic participants in a culturally sensitive manner they will have a higher success rate in their health programs, such as diabetes education programs (Brown, Kouzekanani, Garcia, & Hanis, 2002;Gilmer, Philis-Tsimikas, & Walker, 2005;Gordon, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This approach aligns with the resilience perspective in which English language proficiency is considered an asset. Previous studies document greater access to nutritional advice and resources for English-proficient immigrants compared to non-proficient whereas Spanish preference has been previously correlated with reduced access and use of preventive healthcare services, including nutritional advice [35,36]. Contrary to the second hypothesis, the risk factor household food insecurity was negatively associated with harmful dietary patterns.…”
Section: Discussionmentioning
confidence: 81%